PD-L1 Blockade During Allergen Sensitization Inhibits the Synthesis of Specific Antibodies and Decreases Mast Cell Activation in a Murine Model of Active Cutaneous Anaphylaxis - Bonamichi-Santos, Rafael; Aun, Marcelo Vivolo; Kalil, Jorge; Castells, Mariana Concepcion; Giavina-Bianchi, Pedro (Frontiers in Immunology, 2021)
Programmed cell death ligand 1(PDL-1) is known for its inhibitory effect on the cellular immune response. Even though it is expressed on the surface of mast cells, its role in allergic diseases is unknown. We analyzed the effects of PD-L1 blockade in a murine model of active cutaneous anaphylaxis (ACA). C57BL/6 mice were sensitized and challenged with ovalbumin (OVA). Blood samples were collected to measure specific immunoglobulins. The mice were divided into six groups that underwent the active cutaneous anaphylaxis procedure. Group 1 (negative control) received 50 μl of phosphate-buffered saline (PBS) subcutaneously, and the other five groups were sensitized with 50 μg of OVA subcutaneously. Group 2 was the positive control, and the others received the anti-PD-L1 antibody or its isotype during sensitization (groups 3 and 4) or during the challenge (groups 5 and 6). All animals that underwent ACA on the ears with OVA and PBS were sacrificed, and the reaction was evaluated by extravasation of Evans blue (measured by spectrophotometry) and histological analysis of the collected fragments. Anti-PD-L1 blockade during the sensitization phase led to a reduction in specific IgE and IgG1 levels, allergic reaction intensity at the ACA site, and mast cell degranulation in the tissue. There was no significant biological effect of anti-PD-L1 administration on the challenge phase. PD-L1 blockade during allergen sensitization inhibited the synthesis of specific IgE and IgG1 and decreased mast cell activation in this murine model of anaphylaxis.